2015
DOI: 10.1007/s11999-014-4066-z
|View full text |Cite
|
Sign up to set email alerts
|

No Sex Differences Exist in Posterior Condylar Offsets of the Knee

Abstract: Background Restoration of posterior condylar offset during TKA is believed to be important to improving knee kinematics, maximizing ROM, and minimizing flexion instability. However, controversy exists regarding whether there are important anatomic differences between sexes and whether a unisex knee prosthesis can restore the anatomy of knees in males and females. Questions/purposes The purposes of our study were to determine if sex differences exist in (1) absolute posterior condylar offset size, (2) relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
5
16
0
Order By: Relevance
“…We suspect this is due to the variable nature of the intercondylar fossa. We identified that the medial and lateral PCOs are not symmetrical, corroborating early work suggesting medial PCO is greater than lateral PCO [6,22,23]. While the significance of this is unclear, some authors have suggested that existing arthroplasty systems do not adequately account for a non-uniform PCO [2].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…We suspect this is due to the variable nature of the intercondylar fossa. We identified that the medial and lateral PCOs are not symmetrical, corroborating early work suggesting medial PCO is greater than lateral PCO [6,22,23]. While the significance of this is unclear, some authors have suggested that existing arthroplasty systems do not adequately account for a non-uniform PCO [2].…”
Section: Discussionsupporting
confidence: 83%
“…Wang et al studied 50 male and 50 female Chinese patients and demonstrated that the average PCO of Chinese females (25.80 mm ± 2.71 mm) was significantly smaller than that of Chinese males (27.32 mm ± 2.34 mm), but these authors did not standardize their measurements using the width of the femoral diaphysis and had a very limited population [26]. Our results support those and suggest that PCO is relatively independent of sex, substantiating an MRI study that used standardized measurements [22]. While genderbased knee systems remain a controversial and heavily researched topic, more recent outcome studies have found no difference in genderbased implants [8,10,27].…”
Section: Medial Lateralsupporting
confidence: 86%
See 3 more Smart Citations